Colonisation and extinction in relation to competition and resource partitioning in acanthocephalans of freshwater fishes of the British Isles - Lyndon, A R; Kennedy, C R (Folia parasitologica, 2001)
This paper challenges two paradigms long held in relation to the ecology of parasites in freshwater systems: (1) autogenic species are poorer colonisers than allogenic ones; and (2) parasites with direct life cycles are more successful colonisers than those with complex life cycles. Using new and existing data for Acanthocephala in freshwater fish from the British Isles, it is suggested that all six species present have been able to colonise and persist successfully, in spite of the supposed limitations of their autogenic life-style. It is proposed that these parasites have overcome these limitations by a variety of means, which apply equally to all species considered. Foremost among these is the utilisation of a migratory fish host as either a preferred or a suitable host in their life cycle, allowing colonisation of new areas and rescue effects in established areas, whilst equally important is the use of a common and widespread crustacean as the intermediate host. In addition, all six species appear to exhibit resource partitioning by host at either or both the larval and adult stages, thus reducing the potential for competition and further facilitating colonisation and survival. This hypothesis is supported by data from previous studies both on acanthocephalans from Europe and North America and on other autogenic parasites. It also provides an explanation for the apparently atypical host utilisation patterns of some acanthocephalan species in areas on the edge of their distributions, notably in Ireland.
Keywords: ekologie; druhová specificita; Anglie; Animals; Fresh Water; Ecology; zvířata; Host-Parasite Interactions; Fishes; Species Specificity; interakce hostitele a parazita; sladká voda; England; Acanthocephala; ryby